Importancia de la motricidad y su incidencia en el desarrollo cognitivo en niños de preparatoria de la Unidad Educativa “La Inmaculada” - Varela Varela, Ruth Consuelo (2023)
This research work is developed in the line of research of the Technical University of Cotopaxi, Education and communication for human and social development anchored in the sub line: Psychomotor stimulation and psychomotor development, applied to children at the high school level of the Unit Educational "La Inmaculada" of the Latacunga canton, to determine the shortcomings in psychomotor development that affect the first years of early childhood education, with the general objective: To determine the level of cognitive development through playful strategies in high school children of the Unit Educational "La Inmaculada" in the school year 2022-2023, using the methodology: The present research work will be developed with a quantitative-qualitative approach since the data that will be collected will be subjected to an analysis and interpretation of the results.